Combating rituximab resistance by inducing ceramide/lysosome-involved cell death through initiation of CD20-TNFR1 co-localization. (3rd May 2016) - Zhang, Fan; Yang, Junlan; Li, Huafei; Liu, Moyan; Zhang, Jie; Zhao, Lichao; Wang, Lingxiong; LingHu, RuiXia; Feng, Fan; Gao, Xudong; Dong, Biqin; Liu, Xiaohan; et al.
ABSTRACT: Despite the success of CD20 antibody rituximab in immunotherapy, acquired resistance is one of the prime obstacles for the successful treatment of B-cell malignancies. There is an urgent need to intensify efforts against resistance in cancer treatment. Growing evidence indicated that lysosomes may form an "Achilles heel" for cancer cells by sensitizing them to death pathways. Here, we uncover an important role of CD20 in initiation of ceramide/lysosomal membrane permeabilization (LMP)-mediated cell death, showing that colocalization of CD20-TNFR1 after type II CD20 antibody ligation can stimulate de novo ceramide synthesis by ceramide synthase and consequently induce remarkable lysosomal permeabilization (LMP) and lysosome-mediated cell death. Further studies show that the potent lysosome-mediated cell death induced by CD20 antibodies exhibits a profound killing effect against both rituximab-sensitive and -resistant (RR) lymphoma. Furthermore, engineering of rituximab by introducing a point mutation endows it with the ability to induce potent ceramide/LMP-mediated cell death in both RR lymphoma and primary B-cell malignancies from patients with rituximab-refractory, suggesting the potential clinical application to combat rituximab resistance.